Analisis Efisiensi Pemasaran Sayuran Hidroponik Pakcoy pada Usahatani Amor Kota Tangerang Selatan - Rahmadina, Shelvy; Simbolon, Sehat; Nuralyasari, Putri; Ramadhani, Putri; Jumiyanti, Jumiyanti (Universitas Galuh, 2024)
This research was conducted to determine marketing channels, marketing margins, and farmer share of hydroponic pak choy vegetables in Amor farming, South Tangerang City. This research uses a qualitative and quantitative descriptive approach to analyze the marketing efficiency of pak choy hydroponic vegetables. Data was collected through direct interviews and secondary data from other agencies. The research results show that two marketing channel patterns are formed: pattern I involves farmers and consumers, and pattern II involves farmers, traders and consumers. Pattern II has the highest marketing margin of IDR 9,000, while pattern I has the lowest margin of IDR 0. Therefore, pattern I is more efficient. Farmer share analysis shows that pattern I is the most efficient because farmers sell directly to consumers without involving traders, so they have a farmer share of 100%. It is hoped that the results of this research will become a marketing reference and decision for Amor farming, as well as academic reference material and a source of information about marketing efficiency.